Accuracy Motivations, Predispositions, and Social Information in Political Discussion Networks. Issue 3 (31st March 2015) - Pietryka, Matthew T.
Abstract : This analysis studies how variation in individuals' motivation to form accurate judgments affects the process of political discussion. I use a small‐group experiment in which participants compete to elect the simulated candidate who best represents their true preferences. I manipulate economic incentives to control participants' accuracy motivations. The results show that accuracy‐motivated participants, compared to those with weaker accuracy goals, seek discussants with more expertise and a more diverse set of viewpoints, place greater emphasis on socially provided messages, and reduce emphasis on political predispositions. As a result of these differences, however, accuracy‐motivated participants rely more heavily on biased information. Hence, accuracy motivations do not produce more accurate judgments or better decisions. Although previous work on political discussion has largely ignored the role of motivations, these results suggest that accuracy motivations play an important but nuanced role in this process. Strengthened accuracy motivations increase individuals' exposure to political expertise and ideological diversity but also increase their potential to be misled.